2020
DOI: 10.12965/jer.2040546.273
|View full text |Cite
|
Sign up to set email alerts
|

Multiple athletic performances, maturation, and Functional Movement Screen total and individual scores across different age categories in young soccer players

Abstract: The purpose of this study was to evaluate differences in multiple athletic performances, and to examine associations between athletic performance and Functional Movement Screen (FMS) in young soccer players. Forty-one soccer players were tested on peak height velocity (PHV), 5-, 10-, and 30-m sprint times, 505 change of direction (505 COD), Y-reactive agility tests, countermovement jump (CMJ), and squat jump (SJ) height. Significant main effects ( P <0.01) were recorded in all tests exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 27 publications
0
21
2
Order By: Relevance
“…As a result, the effect size was 0.7109283, α (significant level) was 0.05, and the power of test (1−β) was 80%. Based on this, a total of 24 subjects were calculated to use one-way analysis of variance (ANOVA) to compare balance ability, isokinetic moments, anaerobic ability, and physical fitness of each group ( Bakalľár et al, 2020 ). Therefore, in this study, 35 subjects were selected based on the dropout rate.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the effect size was 0.7109283, α (significant level) was 0.05, and the power of test (1−β) was 80%. Based on this, a total of 24 subjects were calculated to use one-way analysis of variance (ANOVA) to compare balance ability, isokinetic moments, anaerobic ability, and physical fitness of each group ( Bakalľár et al, 2020 ). Therefore, in this study, 35 subjects were selected based on the dropout rate.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the 13 studies identified ( Figure 1 ), all were published between 2015 and 2021. Geographically, studies were conducted in Australia [ 40 ], Italy [ 41 ], Portugal [ 42 ], Slovakia [ 43 ], South Africa [ 44 ], Taiwan [ 45 ], Turkey [ 46 , 47 ], United Kingdom [ 20 , 48 ] and the United States of America [ 27 , 49 , 50 ]. The mean age range across these studies was 11 to 17.40 years, with 2 studies [ 46 , 48 ] exclusively reporting age for boys and girls separately.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies only included male participants [ 20 , 40 , 41 , 43 , 50 ], five studies included a mix of males and females [ 27 , 46 , 47 , 48 , 49 ], while three studies did not explicitly describe the gender of their participants [ 42 , 44 , 45 ]. As such, overall, there were 1649 participants across the studies (minimum = 20, maximum = 981), with 185 reported to be female (11.22%).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a plethora of research on the use of the FMS in adults, there is growing scientific evidence indicating the use of the FMS in youth. Studies to date have been performed in the United States, Canada [ 42 , 43 ], Hungary and Germany [ 44 , 45 ], Italy [ 46 ], Moldova [ 38 ], countries of the UK [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ], Ireland [ 58 , 59 ], Poland [ 60 , 61 , 62 , 63 , 64 ], Slovakia [ 65 ], Iran [ 66 , 67 , 68 ], Turkey [ 69 , 70 , 71 , 72 , 73 , 74 ], Japan [ 75 ], China [ 76 , 77 ], Thailand [ 32 ], Taiwan [ 78 , 79 , 80 ], Korea [ 81 ], Indonesia [ 82 ], Croatia [ 40 , 41 , 83 , 84 ], Brazil [ 85 ], Portugal [ 86 ], Spain [ 87 , 88 , 89 , 90 …”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%
“…Generally, older children perform better on the FMS than younger children [ 50 , 110 ]. In a study of 11 to 15 year old soccer players, there was a non-significant upward trend in the total FMS score from the 11 year-olds (FMS = 15.7), 13 year-olds (FMS = 16) to the 15 year-olds (FMS = 17.2) [ 65 ]. This is in agreement with a recent study [ 45 ] in which there was a weak, but positive correlation between age and the FMS score in 10 to 12 year old girls (0.242) and boys (0.053).…”
Section: The Use Of the Functional Movement Screen In Youthmentioning
confidence: 99%